Possibility of Lightning Strike to Surface-Mounted Antennas on Aircraft - Chowdhury, Soumyadeep; Das, Sayantan; Kumar, Udaya (Amrit Research Journal, 2024)
Lightning is considered a significant electromagnetic hazard for airplanes. One of the initial stages in developing lightning protection systems for airplane involves determining potential areas where lightning may strike and attach to the airplane. The most common mode of attachment to the airplane, known as the airplane-initiated mode, is caused by airplane-initiated bipolar leaders. Previous research has indicated that airplane components, such as the nosecone, wingtips, and stabilizer tips, play a crucial role in the commencement of connecting leaders. Apart from these, other extremities formed by the surfacemounted antennas are also present on the airplane. These antennas are typically 40-50 cm tall, providing sharp protrusions where significant field intensification can occur under the influence of the ambient field. Lightning attachment to the antenna subjects it to high rate of rise of current and large variation in local electric field. Moreover, the initial attachment can result in local intense heating and consequential damage. Therefore, it is crucial to investigate how these surface-mounted antennas are vulnerable to attachment compared to other airplane extremities. The current investigation aims to measure the likelihood of lightning striking antennas on airplane.